PERAN GURU AKIDAH AKHLAK DALAM MENUMBUHKAN KECERDASAN SPRITUAL SISWA DI MADRASAH TSANAWIYAH AL-IRSYAD KELURAHAN KAMPUNG LAUT KECAMATAN KUALA JAMBI KABUPATEN TANJUNG JABUNG TIMUR - Tanjung, Zulkifli; Anaswan, Anaswan; Nisak, Sayida Khoirotun (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2023)
This study aims to reveal about the Role of Aqidah Akhlak Teachers in Growing Students' Spiritual Intelligence at Madrasah Tsanawiyah Al-Irsyad Village of Kampung Laut, Kuala Jambi District, East Tanjung Jabung Regency. The research approach used is descriptive qualitative with data collection techniques of observation, interviews and documentation. While the data analysis technique is done by data reduction, data presentation and drawing conclusions. To verify the reliability of the research results, atriangulation technique was used to meet the criteria of credibility, transferability, dependability and objectivity. The results of the study revealed that: The teacher in cultivating students' spiritual intelligence is carried out by getting used to doing good, providing good examples, as a guide by giving advice, as a motivator by giving punishment and as a link by taking an integrated approach in forming student personalities with other teachers. The constraints of the Aqidah Akhlak teacher in cultivating students' spiritual intelligence are lack of supervision of students, lack of discipline in students, and lack of persistence in seeking knowledge. Solutive efforts by the school to overcome the obstacles of Akidah Akhlak teachers in cultivating students'spiritual intelligence are giving severe punishments and always coordinating with the school principal and opening up cooperation with parents of students in instilling high religious values.